Polyproline II Helix Conformation in a Proline-Rich Environment: A Theoretical Study - Vila, Jorge Alberto (2004)
Interest centers here on whether a polyproline II helix can propagate through adjacent non-proline residues, and on shedding light on recent experimental observations suggesting the presence of significant PPII structure in a short alaninebased peptide with no proline in the sequence. For this purpose, we explored the formation of polyproline II helices in prolinerich peptides with the sequences Ac-(Pro)3-X-(Pro)3-Gly-Tyr-NH2, with X ¼ Pro (PPP), Ala (PAP), Gln (PQP), Gly (PGP), and Val (PVP), and Ac-(Pro)3-Ala-Ala-(Pro)3-Gly-Tyr-NH2 (PAAP), by using a theoretical approach that includes a solvent effect as well as cis $ trans isomerization of the peptide groups and puckering conformations of the pyrrolidine ring of the proline residues. Since 13C chemical shifts have proven to be useful for identifying secondary-structure preferences in proteins and peptides, and because values of the dihedral angles (f,c) are the main determinants of their magnitudes, we have, therefore, computed the Boltzmann-averaged 13C chemical shifts for the guest residues in the PXP peptide (X ¼ Pro, Ala, Gln, Gly, and Val) with a combination of approaches, involving molecular mechanics, statistical mechanics, and quantum mechanics. In addition, an improved procedure was used to carry out the conformational searches and to compute the solvent polarization effects faster and more accurately than in previous work. The current theoretical work and additional experimental evidence show that, in short proline-rich peptides, alanine decreases the polyproline II helix content. In particular, the theoretical evidence accumulated in this work calls into question the proposal that alanine has a strong preference to adopt conformations in the polyproline II region of the Ramachandran map.